So What Do Polar Bears Think about Us? Review of Michael Engelhard, Ice Bear: The Cultural History of an Arctic Icon - Fee, Margery (Humanimalia, 2017)
Michael Engelhard. Ice Bear: The Cultural History of an Arctic Icon. Seattle: University of Washington Press, 2017. xiii, 288 pp. 29.95 (pb)